The enduring effects of the Great Recession on wage growth in the United States - Dean Baker (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2014)
Real wages in the United States have continued to stagnate in the years since the end of the Great Recession. This paper attributes this stagnation directly to the prolonged period of high unemployment. It notes research showing that the only period of sustained wage growth for most of the workforce in the last 3 decades was the period of unusually low unemployment in the late 1990s. Given current economic and political trends, it is unlikely that we will again see a level of unemployment low enough to support broad-based real wage growth in the near future.
Keywords: E66; E62; E31; 330; unemployment; wages; hysteresis